Plant‐Based Diet and Sleep Quality in Adults: Exploring the Role of Lifestyle and Health Mediators - Márcia de Oliveira Lima; Júlia Souza de Melo; Larissa de Lima Soares; Risia Cristina Egito de Menezes; Renan Serenini; Giovana Longo‐Silva (Nutrition Bulletin, 2026)
ABSTRACT This study investigated the association between plant‐based dietary indices (PDI) and sleep quality and examined the mediating roles of lifestyle and health‐related factors. A total of 5260 participants (18–65 years) were included. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). PDI—including overall (oPDI), healthy (hPDI), unhealthy (uPDI), and pro‐vegetarian diet index (PVDI)—was derived from a food frequency questionnaire covering 15 food groups. Associations between each PDI and sleep quality were analysed using linear and logistic regression models, and mediation analyses were performed to assess the effects of potential mediators. Poor sleep quality was reported by 51.12% of participants. Each one‐unit increase in oPDI and uPDI was linked to higher PSQI scores ( β : 0.03; 95% CI: 0.01–0.04 and β : 0.08; 95% CI: 0.01–0.03, respectively) and increased odds of poor sleep. In contrast, higher hPDI and PVDI scores were associated with lower PSQI scores and a 12% reduction in odds of poor sleep quality. Mediation analyses showed that higher oPDI and uPDI worsened sleep, partly through greater depression (32.58%) and less physical exercise (19%), respectively. Conversely, higher hPDI and PVDI improved sleep, primarily through a lower body mass index (11.9% and 22%, respectively). Our findings reveal a nuanced relationship between plant‐based dietary patterns and sleep quality, influenced by lifestyle factors. They highlight the importance of distinguishing between healthy and unhealthy plant‐based foods and considering the intake of animal‐derived foods when developing dietary recommendations to improve sleep health.